Use of Copper in Marine Aquaculture and Aquarium Systems - Roy P. Yanong (EDIS)
FA165, a 7-page fact sheet by Roy P. E. Yanong, discusses the use of “bluestone” or “blue copperas” copper sulfate — basic copper chemistry, chelated copper, toxicity to target and non-target organisms, determining dose, reaching and maintaining desired concentrations, and removing copper from the system. Includes references. Published by the UF Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation, December 2009.